2010
DOI: 10.1253/circj.cj-09-0571
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Lipid Measures and Metabolic Syndrome, Insulin Resistance and Adiponectin - Usefulness of Lipid Ratios in Korean Men and Women -

Abstract: Background: Several reports have raised the possibility that newly addressed lipid measures might be superior to the traditional ones for cardiovascular risk prediction. However, data on the associations between these lipid measures with metabolic syndrome (MetS) is limited. Methods and Results:A cross-sectional study of participants in routine health examinations was performed. The associations between lipid measure variables (total cholesterol (TC), triglycerides (TG), low-density lipoprotein cholesterol (LD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
66
1
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(77 citation statements)
references
References 27 publications
2
66
1
2
Order By: Relevance
“…In our study, TG was found to be an independent predictor of incident DM in both fasting and non-fasting men and non-fasting women. Meanwhile, fasting TG is associated with HOMA-IR in European, Australian Aboriginal, Chinese and Korean individuals 32,33) . Moreover, a decrease in the effects of insulin has been shown to not only increase the TG level, but also decrease the HDLC level, resulting in an increased TG/HDL ratio 33) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, TG was found to be an independent predictor of incident DM in both fasting and non-fasting men and non-fasting women. Meanwhile, fasting TG is associated with HOMA-IR in European, Australian Aboriginal, Chinese and Korean individuals 32,33) . Moreover, a decrease in the effects of insulin has been shown to not only increase the TG level, but also decrease the HDLC level, resulting in an increased TG/HDL ratio 33) .…”
Section: Discussionmentioning
confidence: 99%
“…An impaired insulin function, consisting of insulin resistance and β-cell damage, is a characteristic feature of incident DM 16) . Insulin resistance is associated with TG 6,32) . In our study, TG was found to be an independent predictor of incident DM in both fasting and non-fasting men and non-fasting women.…”
Section: Discussionmentioning
confidence: 99%
“…This is also in favor of the results of our study. 20 Er et al (2016) found triglyceride-glucose index is simple and clinically useful surrogate marker for insulin resistance in non diabetic individuals. 21 The prevalence of metabolic obesity in total study …”
Section: Discussionmentioning
confidence: 99%
“…Leptin is a risk marker for myocardial infarction and hemorrhagic stroke in the population-based cohort. According to the prospective study WOSCOPS cohort on the association between leptin and cardiovascular diseases, leptin was an independent, predictive factor for the incidence of coronary artery disease during a 5-year follow-up [11,12].…”
Section: Discussionmentioning
confidence: 99%